2008
DOI: 10.1002/jsfa.3350
|View full text |Cite
|
Sign up to set email alerts
|

Processing and cooking effects on chemical, nutritional and functional properties of pasta obtained from selected emmer genotypes

Abstract: BACKGROUND: Emmer wheat (T. turgidum ssp. dicoccum Schrank) is an old Mediterranean crop grown for centuries and progressively replaced with durum wheat. Although most of its supposed nutritional properties have not yet been scientifically proven, emmer seems to be appreciated for its content of dietary fibre, resistant starch (RS) and antioxidant compounds. The aim of this work was to evaluate the profiles of dietary fibre, starch and antioxidant compounds in raw materials and in semolina of 13 selected emmer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 40 publications
5
33
0
1
Order By: Relevance
“…Previous researchers have reported that boiling water could degrade sensitive polyphenols or enhance extraction of some bound polyphenols from pasta matrices (Fares, et al, 2008). Interestingly, Supplementary Table 1 X.…”
Section: In Vitro Digestion Of Cooked Pastamentioning
confidence: 94%
“…Previous researchers have reported that boiling water could degrade sensitive polyphenols or enhance extraction of some bound polyphenols from pasta matrices (Fares, et al, 2008). Interestingly, Supplementary Table 1 X.…”
Section: In Vitro Digestion Of Cooked Pastamentioning
confidence: 94%
“…Today it can be found only in some isolated traditional farming communities, in Turkey, Iran, Armenia, Ethiopia, Oman, Italy and Spain (Perrino et al 1996;Hammer et al 2004;Teklu and Hammer 2006. In recent years emmer wheat has been re-discovered by the organic food industry where it is used for bread and cookie production (Caballero et al 2008;Fares et al 2008;Serpen et al 2008). The importance of T. dicoccon landraces has been themed by Teklu et al (2007).…”
Section: Archaeobotanical Finds Of Emmer From the Near Eastmentioning
confidence: 95%
“…In the study by Fares et al (2008) the soluble dietary fibre (SDF) ranged from 1.36 to 2.32%. Regarding SDF, the values found in lines were at the same level as those found by Loje et al (2003) for einkorn and emmer (0.21 -1.74%), but lower than those quoted in the study by Bonafaccia et al (2000) for spelt and common wheat.…”
Section: Dietary Fibrementioning
confidence: 99%